2016
DOI: 10.15654/tpk-150843
|View full text |Cite
|
Sign up to set email alerts
|

Nachweis von Testudinid-Herpesvirus Typ 4 bei einer Pantherschildkröte (Stigmochelys pardalis)

Abstract: ZusammenfassungIn einem Schildkrötenbestand aus Deutschland verstarben mehrere Tiere plötzlich. Einige Pantherschildkröten (Stigmochelys pardalis) aus dem Bestand zeigten respiratorische Symptome. In den von einer erkrankten Schildkröte entnommenen Proben konnten mittels PCR Mykoplasmen und ein Herpesvirus nachgewiesen werden. Die Sequenzierung eines Teils des DNA-Polymerase-Gens des Herpesvirus ergab eine 99%ige Übereinstimmung mit dem Testudinid-Herpesvirus Typ 4, das bisher nur einmal bei einer Afrikanische… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…20 Sequence alignment of the TeHV-4 PCR product showed 99% sequence identity to the TeHV-4 described previously (accession GQ222415.1). 5,36 Remarkably, the PCR product from the pond slider was obtained with the PCR specific for TeHV-1, 49 and sequencing showed 90% sequence identity to TeHV-1 described previously (accession AB047545.1) 49 and 75% sequence identity to TeHV-3 (accession KR363629.1). 20 No product was obtained from this sample using the nPCR protocol.…”
Section: Resultsmentioning
confidence: 61%
“…20 Sequence alignment of the TeHV-4 PCR product showed 99% sequence identity to the TeHV-4 described previously (accession GQ222415.1). 5,36 Remarkably, the PCR product from the pond slider was obtained with the PCR specific for TeHV-1, 49 and sequencing showed 90% sequence identity to TeHV-1 described previously (accession AB047545.1) 49 and 75% sequence identity to TeHV-3 (accession KR363629.1). 20 No product was obtained from this sample using the nPCR protocol.…”
Section: Resultsmentioning
confidence: 61%
“…TeHV4 was found by chance during a quarantine examination of a clinically healthy Bowsprit tortoise (Chersina angulata) at a zoo in the USA (15). It has also been found in a leopard tortoise (Stigmochelys pardalis) in Europe (16). Reported prevalence of testudinid herpesviruses in diagnostic samples from captive tortoises has ranged between 8.2 and 25% (13,(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Another study reported 48.3% prevalence of HV infections in endangered populations of bog ( Glyptemys muhlenbergii ), wood ( G. insculpta ), and spotted ( Clemmys guttata ) turtles in the northeastern United States ( 37 ). Furthermore, tortoise HVs have been associated with high mortality and morbidity ( 104 , 113 , 139 141 ). Different HV species were identified to cause the death of a large number of pancake ( Malacochersus tornieri ), Horsfield ( Testudo horsfieldii ), Hermann's ( Testudo hermanni ), and Egyptian tortoises ( Testudo kleinmanni ) during spontaneous outbreaks in Japan, Italy and Germany, respectively ( 99 , 102 , 142 ).…”
Section: Epidemiologymentioning
confidence: 99%